2019
DOI: 10.1186/s12870-019-2059-5
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between miR156/SPL13 and DFR/WD40–1 regulate drought tolerance in alfalfa

Abstract: Background Developing Medicago sativa L. (alfalfa) cultivars tolerant to drought is critical for the crop’s sustainable production. miR156 regulates various plant biological functions by silencing SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factors. Results To understand the mechanism of miR156-modulated drought stress tolerance in alfalfa we used genotypes with altered expression levels of miR156, miR156-regulated SPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 93 publications
14
112
0
Order By: Relevance
“…A previous report indicated a direct binding of SPL13 to DFR promoter (Feyissa et al, 2019) to enhance anthocyanin biosynthesis. Using the current IPMS analysis, we were able to identify DFR and other candidate proteins interacting with SPL13, such as phenylalanine ammonia-lyase1(PAL1) which catalyses the rst step in the phenylpropanoid pathway by converting phenylalanine to cinnamate (Nuñez-Palenius and Ochoa-Alejo, 2005).…”
Section: Spl13 Interacts With Photosynthesis-and Phenylpropanoid Pathmentioning
confidence: 91%
See 3 more Smart Citations
“…A previous report indicated a direct binding of SPL13 to DFR promoter (Feyissa et al, 2019) to enhance anthocyanin biosynthesis. Using the current IPMS analysis, we were able to identify DFR and other candidate proteins interacting with SPL13, such as phenylalanine ammonia-lyase1(PAL1) which catalyses the rst step in the phenylpropanoid pathway by converting phenylalanine to cinnamate (Nuñez-Palenius and Ochoa-Alejo, 2005).…”
Section: Spl13 Interacts With Photosynthesis-and Phenylpropanoid Pathmentioning
confidence: 91%
“…Physiological investigation of SPL13RNAi plants under drought stress showed maintenance of vital physiological processes, such as photosynthesis and leaf water holding capacity (Feyissa et al, 2019). This was accompanied by an upregulation of photosynthesis-related genes (PSI and PSII) in SPL13RNAi plants (Feyissa et al, 2019).…”
Section: Photosynthesis-related Deg Are Upregulated In Leaves Of Spl1mentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, our group showed that overexpression of miR156 improved multiple physiological traits and altered the transcriptome pro le of alfalfa [30]. Further investigations revealed a positive role for miR156 in abiotic stress tolerance, including drought [26,31], salinity [27] and heat [28]. In addition, transcriptomic analysis showed that miR156 affects a wide array of gene families under drought stress in alfalfa [23].…”
Section: Alfalfa Proteome Is Affected By Mir156 Under Heat Stressmentioning
confidence: 98%